PERAN PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH RADIKALISME DI KALANGAN REMAJA - Nafsiyah, Faizatun; Wardan, Khusnul (STAI Sangatta Kutai Timur, 2024)
Radicalism among teenagers is one of the major challenges in maintaining social stability and security in Indonesia. Islamic Religious Education (PAI) has an important role in shaping the character and morality of adolescents, which can be a bulwark in preventing the entry of radicalism. This article discusses the role of Islamic Education in preventing radicalism among teenagers, influencing factors, challenges and strategies of Religious Education in combating radicalism among teenagers through the cultivation of moderate Islamic values, such as tolerance, compassion, and peace. With a contextual and relevant teaching approach, as well as the role of teachers as role models, PAI can help adolescents understand the essence of religion that is far from violence and extremism. However, challenges in the implementation of religious education, such as the lack of understanding of moderate Islam and the influence of social media, are factors that need to be addressed. This article also offers practical solutions to strengthen the effectiveness of religious education in preventing radicalism among adolescents, by synergistically involving the roles of families, schools and communities. In the end, religious education must continue to be developed in order to be able to give birth to a young generation that is tolerant, peace-loving, and committed to national unity.